Bartonella spp. in bats from the Brazilian Amazon Forest - Franco, Eliz Oliveira [UNESP]; dos Santos, Francisco Chagas Bezerra; de Sousa Verde, Rair; Calchi, Ana Cláudia [UNESP]; de Mello, Victória Valente Califre [UNESP]; Lee, Daniel Braga [UNESP]; Dias, Clara Morato [UNESP]; Machado, Rosangela Zacarias [UNESP]; Carvalho, Adolorata Aparecida Bianco [UNESP]; Roque, André Luiz Rodrigues; André, Marcos Rogério [UNESP] (Springer Nature, 2024)
Despite the great diversity of bats (64 species) in the State of Acre, northwestern Brazil, there are no studies on occurrence and diversity of Bartonella spp. in bats in this region. The present study investigated the occurrence and molecular identity of Bartonella spp. in spleen samples (n = 271) from bats of 30 different species from this region, within the Amazon biome. Twenty-one out of 208 (10.1%) samples positive in the PCR for the mammalian gapdh endogenous genes were positive in the qPCR for Bartonella spp. based on the nuoG gene. The two gltA Bartonella genotypes detected grouped with those previously identified in bats from other locations, expanding the diversity of genotypes associated with bats. This study provided the first molecular evidence of the presence of Bartonella spp. in bats in the state of Acre and in bats of the species Lophostoma silvicolum, Vampyressa thyone, Tonatia saurophila and Phyllostomus elongatus.
Keywords: Acre; Amazon; Bartonella; Chiroptera